On five new species of the genus Synagelides Strand, 1906 (Araneae: Salticidae: Salticinae: Agoriini) from China - Ni, Yi; Li, Yijing; Zhang, Junxia (Zootaxa, 2025)
Five new species of Synagelides Strand, 1906 from China are described: S. numu sp. nov. (♂♀) and S. xiangyun sp. nov. from Hunan Province, S. lovecrafti sp. nov. (♂♀) from Yunnan Province, S. qin sp. nov. (♂♀) from Gansu Province and S. shimian sp. nov. (♂♀) from Sichuan Province. Diagnostic illustrations and photographs, as well as a distributional map, are provided.